Morphometry of the ciliary body and systemic inflammation in neovascular glaucoma secondary to diabetic retinopathy and/or retinal vein occlusion (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To assess ultrasound biomicroscopy (UBM)-based morphometric features of the ciliary body (CB) in patients with neovascular glaucoma (NG) secondary to diabetic retinopathy (DR) anf/or retinal vein occlusion (RVO), and determine their relationships with the stage of rubeosis (according to the Weiss grading system) and systemic inflammation indices (Systemic Immune-Inflammation Index [SII], Systemic Inflammation Response Index [SIRI], and Aggregate Index of Systemic Inflammation [AISI]).Material and Methods: Totally, 160 eyes were included in the study. Of these, 126 had NVG (65 eyes with NVG secondary to DR and 61 eyes with NVG secondary to RVO), and 34 eyes were used as controls. UBM was used to determine CB thickness at a point 1-mm posterior to the sclera spur (CBT1) and maximum CB thickness (CBTmax). The stage of rubeosis was determined according to the Weiss grading system. Spearman rank correlation was used for associations. Multivariate regression analysis with CBTmax as a dependent variable was performed to determine independent predictors of CB thickening.Results: CB thickness was significantly greater in eyes with NVG (1.17–1.50 mm; CBTmax as much as 1.64–1.66 mm) than in controls (CBT1 = 0.82 mm). The greatest values were seen in NVG secondary to RVO (CBT1 = 1.39 mm; CBTmax = 1.66 mm) and NVG secondary to DR with a duration ≤ 5 years (CBT1 = 1.25 mm; CBTmax = 1.63 mm). These values were actually twice as high as normal values, supposing the formation of a hypervoluminous phenotype. Thinning of the CB (CBT1 = 0.57–0.64 mm; CBTmax = 0.74–1.00 mm) was observed in NVG secondary to DR with a duration > 5 years. Systemic indices increased with the stage of rubeosis: SII was increased more than twofold, AISI was increased 2.5–3-fold, and SIRI was increased 1.3–2-fold compared with controls.Conclusion: NVG is accompanied by stage-dependent morphometric changes in the CB, which is manifested by the formation of a hypervoluminous or atrophic phenotype depending on disease etiology and duration. CB thickness demonstrates a close relationship with systemic immune inflammation and rubeosis activity, which highlights its clinical and potential prognostic value.
Keywords: neovascular glaucoma; diabetes mellitus; ultrasound biomicroscopy; ciliary body thickness; systemic inflammation; rubeosis; iris; glaucoma; ciliary body